A Review of Tertiary Referrals for Management of Pediatric Esophageal Eosinophilia - Godwin, Bridget; Liacouras, Chris; Mehta, Vijay; Eisenberg, Joshua; Agawu, Atu; Brown-Whitehorn, Terri; Ruffner, Melanie A.; Verma, Ritu; Cianferoni, Antonella; Spergel, Jonathan M.; Muir, Amanda B. (Frontiers in Pediatrics, 2018)
Background:Eosinophilic esophagitis is a chronic, immune-mediated disease characterized by symptoms of esophageal dysfunction and > 15 eosinophils/high-powered field (eos/hpf). Proton pump inhibitor responsive esophageal eosinophilia 1 is an entity of esophageal eosinophilia that responds to PPI therapy and is thought to be clinically and histologically similar to EoE. Current guidelines suggest therapy with PPI prior to endoscopy and use of PPI as first line for esophageal eosinophilia. In order to gain a better understanding of community practice patterns and to try differentiate between these two entities, we sought to evaluate the clinical presentations, treatment and final diagnoses of patients presenting to our institution for second opinions of esophageal eosinophilia. Methods: A search of our electronic medical record yielded a list of patients presenting for a second opinion of esophageal eosinophilia. Charts were reviewed for clinical information. Results: A total of 187 charts were included. Patients ranged from 1-19 years old with 75% being male and 74% being Caucasian. Of the patients who had documentation of their medications at the time of initial endoscopy, 70% were not on any PPI prior to their endoscopy, and 94% were on < 2mg/kg/day. Of the 19 patients who had full response to PPI therapy and were diagnosed with PPI-REE, close to half had previously been treated with diet, steroids, or both. Patients with final diagnosis of EoE had significantly higher eos/hpf on initial endoscopy compared to those with diagnosis of PPI-REE (51.9±30.6 v. 35.8±16.4. p=0.027), as well as higher likelihood of having IgE-mediated food allergy (79% v. 47%, p=0.003). Conclusions: Diagnostic and therapeutic algorithms are needed for esophageal eosinophilia to prevent misdiagnosis and unnecessary procedures and therapies.